2014
DOI: 10.1039/c4ra10691a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of fully biobased aromatic polyols – oxybutylation of condensed tannins towards new macromolecular architectures

Abstract: For the first time, different tannins were oxybutylated to obtain aromatic and fully biobased polyols. The main interest in using 1,2-butylene oxide (BO) instead of e.g., propylene oxide is because BO can be easily biobased and biosynthesized from biomass. BO can be obtained by epoxidation of butane, produced from biobased butanol, synthesized by biotechnological means. The oxybutylation was carried out using potassium hydroxide as a catalyst, in a high-pressure batch reactor, without solvent, in agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…The worldwide annual production of lignins and tannins is around1 00 kt (Kraft, soda, ando rganosolv processes) [1] and 200 kt, [2] respectively.H owever,l arge increasesa re possible especially for lignin, because only approximately 2% of the lignins fractionated from biomass in paper pulp mills are actuallyi solated. [4][5][6][7] Lignins and tannins can be used as aliphatic poly-ols after,f or example, oxyalkylation, [8][9][10][11][12] fori nstance in polyurethanes. [4][5][6][7] Lignins and tannins can be used as aliphatic poly-ols after,f or example, oxyalkylation, [8][9][10][11][12] fori nstance in polyurethanes.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide annual production of lignins and tannins is around1 00 kt (Kraft, soda, ando rganosolv processes) [1] and 200 kt, [2] respectively.H owever,l arge increasesa re possible especially for lignin, because only approximately 2% of the lignins fractionated from biomass in paper pulp mills are actuallyi solated. [4][5][6][7] Lignins and tannins can be used as aliphatic poly-ols after,f or example, oxyalkylation, [8][9][10][11][12] fori nstance in polyurethanes. [4][5][6][7] Lignins and tannins can be used as aliphatic poly-ols after,f or example, oxyalkylation, [8][9][10][11][12] fori nstance in polyurethanes.…”
Section: Introductionmentioning
confidence: 99%
“…The reported procedures for alkoxylation are quite varied, such as room temperature reactions in solvent (García et al, 2013), pressure controlled reactions through gradual addition of PO monomer into the reactor (Yoshioka et al, 2013), and higher pressure/higher exothermic reaction conditions that utilized PO as a solvent. Alkoxylation has already been performed on a variety of biomass resources such as chitin/chitosan, (Fernandes et al, 2008) cork (Evtiouguina et al, 2001), date seeds (Briones et al, 2011), lignin (Cateto et al, 2010;Nadji et al, 2005;Wu and Glasser, 1984), inulin, (Rogge et al, 2005) starch, (Yoshioka et al, 2013) sugar beet (Pavier and Gandini, 2000a,b), tannin (Arbenz and Avérous, 2014;García et al, 2013) and terpenes (De Meireles et al, 2014). Although lignin and tannins are both components in bark, bark has a wide variety of other extractive compounds and therefore its alkoxylation behavior could vary significantly from what has been reported previously by the literature.…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, the previous work done on tannins was performed at room temperature, (García et al, 2013) as opposed to 180 • C in this work. The work done by Arbenz and Avérous (2014) contrasted the oxybutylation behavior of different tannins and showed that a 100% bio-based polyol could be synthesized by using biosourced butylene oxide, instead of propylene oxide.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations